Influence of the Complex Yersinia pestis EV Antigenic Preparation Upon the Functional Activity of the Phagocytic System Cells Under Experimental Conditions - V. I. Dubrovina; E. P. Golubinsky; S. A. Vityazeva; E. Yu. Markov; V. B. Nikolayev; T. A. Ivanova; Zh. A. Konovalova; T. T. Shkaruba (Проблемы особо опасных инфекций, 2008)
Effects of Y. pestis EV antigenic complexes upon the functional activity of the phagocytic cells of guinea pig and white mice were assayed to demonstrate that the preparation constructed on the basis of the F1 antigen, Y. pestis EV membrane fraction and the Siberian larch arabinogalactane (AG) used as an immunomodulator, was able to increase the functional activities of the phagocytic system in test animals (guinea pigs), enhancing the adhesive and absorptive activity of the peritoneal macrophages and the intensity of active oxygen and nitrate monoxide production, as well as stimulating the activity of myeloperoxidase and the synthesis of non-enzyme cationic polymorphonuclear leucocytes. The antigenic complex prepared on the basis of the F1 antigen, Y. pestis EV membrane fraction and AG, was also shown to exert a stimulating effect on cytokine-inducing function of white-mouse macrophages expressed in the increased production of IL-1, IL-6 and FNO-α cytokines.